Correlation of LIF and Glycodeline an in Prediction of Embryo Implantation of Infertile Women with and without PCOS - Zena F. Hussien (Journal of Global Pharma Technology, 2018)
Implantation of the blastocysts into the maternal uterus is a crucial step in mammalian reproduction, which is controlled by a number of complex molecules like hormones, cytokines, and growth factors and their cross talk. A network of these molecules plays a crucial role in preparing receptive endometrial and blastocysts. This study aimed to found out the role of Glycodeline A,LIF gene expression, concentration, in the endometrial that may interfere with implantation process of polycystic ovary syndrome (PCOS) and non-PCOS women, A convenient blood sample of 80 infertile women undergoing in vitro fertilization (IVF) program were intentionally divided according to the cause of infertility into 40 healthy women their husbands complaining from male infertility factors, and 40 infertile women with polycystic ovary syndrome. Glycodeline A, LIF were measured on ovulatory and luteal phase of cycle (CD14-CD16,17) at the day of ovarian pickup and embryo transfer by using quantitive polymerase chain reaction (qPCR ) and Elisa technique , Results of the present study showed that The gene expression of PAEP ,LIF in addition to levels of serum(Glycodeline A, LIF) were more valuable in predicting the pregnancy out come in infertile PCOS women than in non-PCOS women This result can be utilized to be used as predictors of implantation window for successful implantation and pregnancy.Keywords: Implantation, Glycodeline A, PCOS, IVF program, LIF.